Determinants of Citizens' Perceptions of Police Behavior During Traffic and Pedestrian Stops. (March 2021) - Carmichael, Jason; David, Jean-Denis; Helou, Ann-Marie; Pereira, Colby
A large body of research has examined public perceptions of police behavior. Many of these studies have raised concerns about perceptions of unequal treatment of citizens by law enforcement and the effects such disparate treatment might have on police–community relations. This scholarship has largely examined global perceptions of police behavior rather than asking about actual encounters with officers. Relying on global opinions of police, however, tends to distort perceptions as it tends to illicit prejudiced and stereotypical views about law enforcement rather than lived experiences. This article offers a more precise approach to measuring police behavior during encounters with citizens by assessing views of those who have had recent contact with law enforcement. Specifically, we examine how perceptions of police behavior during both traffic stops and street stops of pedestrians might vary according to a citizen's sociodemographic background and geographic location and how such factors might influence perceptions of the legitimacy of their encounter with the officer. Results from our multivariate analyses suggest that youth, African Americans, the poor, and those living in large urban areas are significantly more likely than others to believe they were treated outside of the scope of acceptable police conduct. Furthermore, ethnic minorities, the poor, and those in urban areas are much more likely to perceive the stop as illegitimate. Our results suggest that much of this might be explained by differences in police behavior according to the size of the place and across different social groups.